Designing Plastic Parts for Assembly. - Tres, Paul A., ....- (Munich : Hanser Gardner Publications, 2014)
"Designing Plastic Parts for Assembly" provides an excellent tool for both seasoned part designers and novices to the field, facilitating cost effective design decisions and ensuring that the plastic parts and products will stand up under use. The detailed yet simplified discussion of material selection, manufacturing techniques, and assembly procedures will enable the reader to evaluate plastic materials and to adequately design plastic parts for assembly. The book describes good joint design and implementation, the geometry and nature of the component parts, the types of load involved, and other basic information necessary in order to work successfully in this field. Throughout, the treatment is practice-oriented and focused on everyday problems and situations. The 7th edition introduces a completely new chapter on overmolding and in-mold assembly, as well as a new chapter on bonding, including accompanying examples. Laser molding and ultrasonics coverage are also brought up to date, with illustrative case histories.